SPATIAL MAPPING OF COCONUT (Cocos nucifera L.) PLANTATIONS IN SANGKUB DISTRICT, NORTH BOLAANG MONGONDOW REGENCY USING GEOGRAPHIC INFORMATION SYSTEMS - Nadia Jovanka Rombe; Wiske Ch. Rotinsulu; Sandra E. Pakasi (Jurnal Agroekoteknologi Terapan, 2021)
Coconut plants have many benefits for human life and also as a source of foreign exchange through exports. Sangkub District is one of the coconut-producing sub-districts in North Sulawesi Province. To see the distribution of coconut plants in Sangkub sub-district, it is necessary to do a spatial mapping using a Geographic Information System to see the condition of the plantation. The purpose of this study was to determine the area of coconut plantations and to see the distribution of plantations in Sangkub District. From the results of the spatial mapping that has been carried out, the distribution of coconut plantations in Sangkub District is spread over several villages, namely in the villages: Sangtombolang, Sampiro, Sangkub I, Sangkub II, Sangkub III, Tombolango, Busisingo, Sidodadi, North Busisingo, Sangkub IV, East Sangkub, and Suka Makmur. For the area of distribution of coconut plantations, the largest is in the village of Sangklikang with an area of 441 hectares and the smallest is in the village of Suka Makmur with an area of 1 hectares.Â Keywords: Spatial Mapping; Coconut Plantation; Geographic Information System.AbstrakTanaman kelapa memiliki banyak manfaat bagi kehidupan manusia dan juga sebagai sumber devisa negara melalui ekspor. Kecamatan Sangkub merupakan salah satu kecamatan penghasil kelapa di Provinsi Sulawesi Utara. Untuk melihat penyebaran tanaman kelapa yang ada di kecamatan Sangkub, maka perlu dilakukan pemetaan spasial menggunakan Sistem Informasi Geografis guna melihat kondisi dari perkebunan tersebut. Tujuan penelitian ini untuk mengetahui luas lahan perkebunan kelapa dan melihat penyebaran dari perkerkebunan di Kecamatan Sangkub. Dari hasil pemetaan spasial yang telah dilakukan, penyebaran perkebunan kelapa di Kecamatan Sangkub tersebar di beberapa desa yaitu pada desa : Sangtombolang, Sampiro, Sangkub I, Sangkub II, Sangkub III, Tombolango, Busisingo, Sidodadi, Busisingo Utara, Sangkub IV, Sangkub Timur, dan Suka Makmur. Untuk luas penyebaran perkebunan kelapa terbesar berada di desa Sangtombolang dengan luasan 441 Ha dan yang terkecil berada di desa Suka Makmur dengan luasan 1 Ha. Sedangkan untuk desa yang tidak terdapat penyebaran perkebunan kelapa yaitu pada desa Pangkusa, Apeng Sembeka, Monompia, dan Mokusato.Kata Kunci: Pemetaan Spasial; Perkebunan Kelapa; Sistem Informasi Geografis